Strategic Marketing Analysis of Club Roppang Toast: Enhancing Competitiveness through Capital Optimization and Consumer-Centric Approaches - Fanianto, Eka Rachmad; Lestari, Datik (Politeknik Negeri Jember, 2024)
Club Roppang Toast Business is a business in the agro-industry sector located on Jalan Srikoyo, Patrang District, Jember Regency, East Java. This business produces toast with various flavors such as sweetened condensed milk, butter, sugar, oreo, chocolate, beng beng, milo, jasuke, honey, choco mozz, cheese, smoked beef. The purpose of this study is to determine the right marketing strategy to be used by the Club Roppang business in order to compete and develop in the future. The method used in this study is the SWOT and QSPM methods, so that several strategic results can be obtained, including (1) Improving good service and maintaining product quality so that consumers remain loyal (2) Adjusting the attractiveness of the Roppang club with changes in lifestyle and as the population increases (3) Increasing the capital used to be able to meet the purchase of raw materials so that it can increase people's purchasing power (4) Carrying out modern recording so that the purchase of raw materials is more efficient so that it can compete with similar products (5) Re-adjusting the prices that have been set with the increasing population so that it increases consumer loyalty (6) Improving less efficient production equipment with the development of technology so that it can adjust to changes in people's lifestyles (7) Competing on price by adjusting the price of raw materials so that it can increase people's purchasing power (8) Optimizing less strategic locations by utilizing promotional media so that it can compete with similar products. Of the eight strategies, the most important results were obtained, namely carrying out a strategy to increase the capital used to be able to meet the purchase of raw materials so that it can increase people's purchasing power.